Analyzing the Use of the (PATROL) Early Warning Model in Assessing the Financial Performance of The Banking Sector in Iraq - Saif-Allah, Haider Ali; Abbas, Salah Mahdi (Journal of Economics and Administrative Sciences, 2025)
This paper describes the financial performance of the banking sector in Iraq using the PATROL early warning model. The research found the strengths and weaknesses in bank operations and forecasted the financial crises using data from 2018 to 2022 to enhance performance. The indicators included capital adequacy, credit risk, profitability, organizational efficiency, and liquidity, with performance rated on a scale from "very good" to "poor." Related findings proved that the Iraqi banks would be entirely successful in financial performance regarding most indicators and scaling-high in capital adequacy, profitability, organization, and liquidity, in accordance with sound management and robust operations. However, credit risk posed challenges because the assets demonstrated lower quality compared to other indicators. Findings from the research suggest the importance of the PATROL model in guiding regulatory authorities in monitoring financial health, correcting imbalances, and improving stability. Overall, the empirical study tends to validate the effectiveness of the model as a strategy for improving and assessing financial outcomes in the banking sector. The research study has been geared towards the analysis of the financial performance of the banking sector in Iraq using the PATROL early warning model. The research found strengths and weaknesses in bank operations and predicted the financial crises using data from the years 2018 to 2022 to enhance performance. The indicators included capital adequacy, credit risk, profitability, organizational efficiency, and liquidity which were rated with respect to performance on a scale from "very good" to "poor." Related findings proved that the Iraqi banks would be entirely successful in financial performance regarding most indicators and scaling-high: capital adequacy, profitability, organization, and liquidity according to sound management and robust operations. However, credit risk posed challenges, which showed lower quality assets compared to other metrics. The research points out the usefulness of the PATROL model in guiding regulatory authorities to monitor the financial health, correct imbalances, and improve stability. In general, the empirical study seems to affirm the efficacy of the model as a scheme for assessing and improving financial outcomes not just for the banking sector, but for all sectors.